Impact of Acquisition Processes on Turnover Intention and Commitment Among Employees of Universal Merchant Bank, Accra - Sassah, M. (University of Ghana, 2015)
This study investigated the impact of acquisition processes on turnover intention and commitment among employees of Universal Merchant Bank (UMB). The study which employed a mixed method was carried out in six main branches of UMB in Accra. Purposive, Stratified and convenience sampling techniques were used in selecting the branches as well as the 188 survey respondents plus 4 interviewees. Structured questionnaires together with an interview guide were adapted as instruments for data collection. The data was analyzed using descriptive, inferential and thematic methods for the quantitative and qualitative data respectively. The study revealed that acquisition processes has an insignificant relationship with the turnover intention of employees because they did not feel much job insecurity. It was also found that in the context of an acquisition, both the affective and normative components of employees’ commitment were not significantly affected except the continuance component. The study again found that most of the employees were staff of Merchant bank before its acquisition and seemed to realize more opportunities awaiting them in the bank now and hence, did not show any intention of leaving. Based on these findings, it was argued that, in the context of an acquisition, employees’ commitment is a “need- based” organizational phenomenon rather than “want” or “obligation” because the acquirer ends up ruling out most of the “favorite cultural practices and norms” of the acquired company’s employees and introducing its new core values. It was recommended that management of UMB should design job-specific training for employees to equip them with relevant KSAs needed for their new job demands and other responsibilities since most of employees’ jobs have been enlarged. It is equally recommended that management of the bank organize more seminars to elaborate the essence of the new core values of the firm and the need for employees to embrace them as early as possible to bridge any gaps of cultural misfit.
Thesis (MPhil.)
Keywords: Acquisition; Employees; Turnover; Ghana